Rescue of PFOS-induced human Sertoli cell injury by overexpressing a p-FAK-Y407E phosphomimetic mutant. Issue 1 (December 2017) - Chen, Haiqi; Gao, Ying; Mruk, Dolores; Xiao, Xiang; John, Constance; Turek, Paul; Lui, Wing-yee; Lee, Will; Silvestrini, Bruno; Cheng, C.
Abstract PFOS induces Sertoli cell injury using testicular cells isolated from rodent testes, but it remains unknown if PFOS has similar effects in humans. Herein, we maintained human Sertoli cells in a mitotically active statein vitro, thus enabling transfection experiments that altered gene expression to explore the molecular mechanism(s) underlying toxicant-induced cell injury. Human Sertoli cells obtained from men at ages 15, 23, 36 and 40 were culturedin vitro . These differentiated Sertoli cells remained mitotically active when cultured in the presence of 10% FBS (fetal bovine serum), with a replication time of ~1–3 weeks. At ~80% confluency, they were used for studies including toxicant exposure, immunoblotting, immunofluorescence analysis, tight junction (TJ)-permeability assessment, and overexpression of BTB (blood-testis barrier) regulatory genes such as FAK and its phosphomimetic mutants. PFOS was found to induce Sertoli cell injury through disruptive effects on actin microfilaments and microtubule (MT) organization across the cell cytosol. As a consequence, these cytoskeletal networks failed to support cell adhesion at the BTB. Overexpression of a FAK phosphomimetic and constitutively active mutant p-FAK-Y407E in these cells was capable of rescuing the PFOS-induced injury through corrective cellular organization of cytoskeletal elements. Summary: PFOS induces human Sertoli cell injury which can be rescued by overexpressing p-FAK-Y407E mutant.